2017
DOI: 10.1002/pon.4501
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a group intervention to facilitate posttraumatic growth among women with breast cancer

Abstract: Objective: This longitudinal study tested the effectiveness of a group intervention designed to facilitate posttraumatic growth (PTG).Methods: Sample consisted of 205 women diagnosed with non-metastatic breast cancer who were either assigned to an intervention group (n = 58) or to a control group (n = 147). PTG, challenge to core beliefs, and rumination (intrusive and deliberate) were assessed at baseline (T1), at 6 months (T2), and at 12 months after baseline (T3). Results:Results from the Latent Growth Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 30 publications
0
32
0
4
Order By: Relevance
“…The second one is that only the total score of rumination was evaluated, and not different forms of rumination. Studies that have shown correlation between this variable and PTG (15,29) included the differences of types of rumination and ways of doing so in relation to PTG. Therefore, the evaluation of different types and individual ways of rumination must be evaluated in order to verify if any of those would be found to be explanatory for this model in this sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second one is that only the total score of rumination was evaluated, and not different forms of rumination. Studies that have shown correlation between this variable and PTG (15,29) included the differences of types of rumination and ways of doing so in relation to PTG. Therefore, the evaluation of different types and individual ways of rumination must be evaluated in order to verify if any of those would be found to be explanatory for this model in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…Later, other studies pursued the establishment of variables that were correlated to a greater PTG score and that explained this model (9,(12)(13)(14) . Different authors concluded that rumination, social support, the use of adaptive coping strategies and the perception of the experienced situation as actually stressing have proven to be major predictors of a greater PTG (11,14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…From the analyzed studies, five opted to use cultural adaptions of the original PTGI (24)(25)(26)(27)(28) . Only in the studies of Chan et al (25) e Tomita et al (28) the adapted instruments went through alterations in the amount of items and factors.…”
Section: Posttraumatic Growthmentioning
confidence: 99%
“…Three articles evaluated and analyzed rumination in their samples. In two studies this variable was included in the main objective (25,33) , and in one it was used as a benchmark variable of differences between compared groups (27) .…”
Section: Ruminationmentioning
confidence: 99%
See 1 more Smart Citation